Online teaching during the COVID-19 pandemic: A case study of Albania - Irida Hoti; Blerta Dragusha; Valentina Ndou (Administrative Sciences, 2022)
The spread of COVID-19 has caused the interruption of education in all levels of schools, forcing them to seek urgent solutions to reconfigure traditional education programs for distance learning. The emergency restrictions related to social distancing, gathering, etc., have generated a disruption, resulting in a massive quick shift to distance and online teaching. The disruption of teaching has been highly critical and complex, especially for developing countries due to the lack of technological infrastructure, low Internet access, low level of preparation of teachers and parents to use technology, and lack of learning motivation. This paper aimed at identifying the main teaching practices, challenges, and contextual characteristics that impacted the adoption and use of online teaching solutions, during the COVID-19 outbreak, in a developing country, Albania. The paper reached this goal by providing the results of a survey involving 100 educators from different levels of public education institutions in Albania (high schools and universities). The results revealed that despite a set of challenges faced, the online teaching experience during the pandemic time brought improvements in computer teaching skills and communication with students by using several applications for interactivity.
Keywords: 350; education; technology; Albania; challenges and opportunities; online teaching